Un raton fugitivo llamado Ralph - Cleary, Beverly; Darling, Louis (Barcelona : Planeta, 1981)
Ralph runs away looking for freedom but winds up a prisoner at a summer camp.
Titulo original : Runaway Ralph.
Text in Spanish.
Keywords: Mice -- Fiction